Odd-even oddball task: Evaluating event-related potentials during word discrimination compared to speech-token and tone discrimination - Voola, Marcus; Nguyen, An T.; Marinovic, Welber; Rajan, Gunesh; Tavora-Vieira, Dayse (Frontiers in Neuroscience, 2022)
Tonal and speech token auditory oddball tasks have been commonly used to assess auditory processing in various populations; however, tasks using non-word sounds may fail to capture the higher-level ability to interpret and discriminate stimuli based on meaning, which are critical to language comprehension. As such, this study examines how neural signals associated with discrimination and evaluation-processes (P3b) from semantic stimuli compare with those elicited by tones and speech tokens. This study comprises of two experiments, both containing thirteen adults with normal hearing in both ears (PTA ≤ 20 dB HL). Scalp electroencephalography and auditory event related potentials were recorded in free field while they completed three different oddball tasks: (1) tones, (2) speech tokens and (3) odd/even numbers. Based on the findings of experiment one, experiment two was conducted to understand if the difference in responses from the three tasks was attributable to stimulus duration or other factors. Therefore, in experiment one, stimulus duration was not controlled and in experiment two, the duration of each stimulus was modified to be the same across all three tasks (∼400 ms). In both experiments, P3b peak latency was significantly different between all three tasks. P3b amplitude was sensitive to reaction time, with tasks that had a large reaction time variability resulting in the P3b amplitude to be smeared, thereby reducing the amplitude size. The findings from this study highlight the need to consider all factors of the task before attributing any effects to any additional process, such as semantic processing and mental effort. Furthermore, it highlights the need for more cautious interpretation of P3b results in auditory oddball tasks.